The 15-year trend in adherence to dietary recommendations and ultra-processed food consumption in Italy - Di Veroli, Jacopo Niccolò; Capruzzi, Sara; Scognamiglio, Umberto; Rossi, Laura (Frontiers in Nutrition, 2025)
IntroductionDiet quality indices are essential tools for evaluating dietary patterns in relation to health and sustainability. This study aims to assess the quality of the Italian diet using the Adherence to Italian Dietary Guidelines Indicator (AIDGI) and World Index for Sustainability and Health (WISH2.0) and to estimate ultra-processed food (UPF) consumption as an indicator of poor diet quality.MethodsItalian food consumption data from 2005 to 2006 and 2018 to 2020 were sourced from the European Food Consumption Comprehensive Database. The dataset includes a wide range of foods categorized by age and sex; for this analysis, two population groups were considered: adults (18–64 years) and the elderly (65–74 years).ResultsThe sample sizes included 2,313 adults and 290 elderly individuals in 2005–2006 and 726 adults and 156 elderly individuals in 2018–2020. AIDGI and WISH2.0 showed scores close to 50% of the theoretical maximum achievable indicating that there is substantial room for improvement in the Italian dietary quality. Older adults, particularly women, exhibited healthier eating habits compared to younger adults and men.DiscussionsA temporal trend was observed, having different characteristics in adults and the elderly. Both AIDGI and WISH2.0 scores indicated a more favorable change over time in the elderly compared to adults (AIDGI: +5.6% in the elderly, −5.9% in adults; WISH2.0: +2.8% in the elderly, −5.1% in adults). Although ultra-processed foods (UPFs) accounted for only 6% of total food consumption by weight in 2018–2020, they contributed to 23% of total energy intake. Despite only a modest increase in their consumption by weight, their percentage of energy intake has nearly doubled compared to 2005–2006. In contrast, the consumption of processed foods (PFs) decreased in terms of weight, from 16 to 11%, while their contribution to energy intake remained relatively stable (~28%).ConclusionsThis study reveals a gradual decline in the quality of Italian diets over time, primarily reflected in the increasing consumption of UPFs and distinct demographic patterns. While overall adherence to dietary recommendations appears relatively stable, this may partly reflect the fact that current guidelines do not explicitly differentiate between UPFs and minimally processed foods—an aspect with important implications for public health.